Metallographic analysis of an iron vessel fragment from the Late Saka kurgan of the Kyzylzhartas burial ground, Central Kazakhstan - Beisenov A.Z.; Panichkin A.V. (Вестник археологии, антропологии и этнографии)
Two fragments of the rim of an iron vessel have been found in mound 2 of the Kyzylzhartas cemetery located in the Shet district of the Karaganda region. The mound, 34 m in diameter and 1.4–2 m high, represents a burial site of the elite of the Late Saka period. This status of the burial is also confirmed by the gold jewellery that survived the robbery of the mound in ancient times. Based on archaeological data and radiocarbon analysis, the mound is dated to the second half of the 4th–3rd centuries BC. Metallographic analysis of single rim has shown that the vessel was manufactured from an iron sheet, 0.8–1 mm thick, made from a bloom by forging. The edge of the rim is bent inwards, and two circular hoops made from the same sheet are placed on the outside to strengthen the neck of the vessel. The lower one is a narrow strip bent at an obtuse angle. A second hoop is positioned on top of it, folded along its length from ca. 10 mm wide strip, with a cross-section in the shape of a flattened “eight”. The rim of the vessel is decorated with an ornament of a strip of yellow paint. The analysis of the structure of the paint layer suggests that the pigment was obtained from the mineral brown iron ore, otherwise limonite, by the means of grinding. Vessels of the late Saka period, made of iron sheet, are unknown on the territory of Kazakhstan. It was not possible to find any similarities in neighbouring regions as well. The results of the study are published for the first time.